Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675194
|View full text |Cite
|
Sign up to set email alerts
|

Connecting in the Kitchen

Abstract: Recent research has explored the role technology might play in future kitchens, including virtually dining together, recipe sharing, augmented kitchen furniture, reactive cooking utensils and gestural interaction. When people come together in a kitchen to cook it is about more than just production of sustenance -it is about being together, helping each other, exchanging stories, and contributing to the gradual emergence of a shared meal. In this paper we present a digital ethnography of how people coordinate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Food production, distribution and consumption have recently attracted growing attention in the field of HCI [7,8,16,[34][35][36]. Cooking is a cross-cultural practice that supports communities by bringing people together, enabling communality, solidarity, and leading to commensality: shared meals and community building [43,44].…”
Section: Background 21 Cooking and The Kitchen In Human-food Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…Food production, distribution and consumption have recently attracted growing attention in the field of HCI [7,8,16,[34][35][36]. Cooking is a cross-cultural practice that supports communities by bringing people together, enabling communality, solidarity, and leading to commensality: shared meals and community building [43,44].…”
Section: Background 21 Cooking and The Kitchen In Human-food Interactionmentioning
confidence: 99%
“…Cooking skills, recipes and techniques are shared with families and networks through informal and formal interactions [44]. Therefore, technology design needs to consider the social, collaborative and experiential aspects of cooking [34][35][36]. To describe the complexity of cooking together with others, Paay et al [35] identified three distinct task-related configurations: working on related tasks, working on independent tasks, and working on shared tasks.…”
Section: Background 21 Cooking and The Kitchen In Human-food Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early work on F-formations focused on interpersonal interactions around large public displays and/or physical structures. Examples of this include the work by Marquardt et al (2012) who observed groups of participants performing joint activities around a tabletop interface in a tourist information center, or the work by Paay et al (2015), who studied F-formations in kitchens, focusing on the architectural design of the kitchen. This first wave of studies revealed that F-formations vary with the task and that physical structures in the space encourage certain formations (Marshall et al, 2011a;Marshall et al, 2011b).…”
Section: Proxemic Interactionsmentioning
confidence: 99%